PERKEMBANGAN DAN PERUBAHAN KURIKULUM DI SEKOLAH DASAR FITRIAH RAHMAH - Dwika Aulia Fitrah Panjaitan; Juliana Juliana; Nada Syiva Salsabila; Naina Idma Siregar; Nazirah Al Zany; Raja Siregar (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Curriculum is a set of plans and arrangements regarding objectives, content and learning materials as well as the methods used as guidelines for the implementation of learning activities to achieve certain educational goals. These specific goals include national education goals as well as conformity with regional characteristics, conditions and potential, educational units and students. Therefore, the curriculum is prepared by the education unit to enable the adjustment of educational programs to the needs and potential that exist in the region. The preparation of this set of subjects is adjusted to the conditions and abilities of each level of education in the implementation of such education and the need for employment. The length of time in one curriculum is usually adjusted to the aims and objectives of the implemented education system. This curriculum is intended to be able to direct education towards the intended direction and goals in learning activities as a whole. The curriculum is a guide for an educator to provide good material and knowledge to students, the curriculum also has developments and that is why the importance of the role of the curriculum must be understood